Use of n-alkanes to estimate feed intake in ruminants: a meta-analysis. (10th September 2020) - Andriarimalala, Jose Herilalao; Dubeux, Jose Carlos B; DiLorenzo, Nicolas; Jaramillo, David Mirabedini; Rakotozandriny, Jean de Neupomuscène; Salgado, Paulo
Abstract: Precise techniques to estimate feed intake by ruminants are critical to enhance feed efficiency and to reduce greenhouse gas emissions and nutrient losses to the environment. Using a meta-analysis, we evaluated the accuracy of the n -alkane technique to predict feed intake in cattle and sheep and assessed the relationships between feed intake and fecal recovery (FR ) of n -alkanes. The database was composed of 28 studies, including 129 treatments (87 and 42 for cattle and sheep, respectively) and 402 animals (232 cattle and 170 sheep) fed at troughs, from published studies. Relationships between observed (in vivo measurement) and predicted feed intake by C31:C32 and C32:C33 n -alkane pairs were evaluated by regression. Meta-regression addressed the relationships between the difference in FR of n -alkane pairs and the error in intake estimation, as well as the amount and duration of C32 n -alkane dosing. Regression of observed intake on n -alkane-based estimates revealed good relationships in cattle (adjusted R 2 = 0.99 for C31:C32, and adjusted R 2 = 0.98 for C32:C33; P < 0.0001) and in sheep (adjusted R 2 = 0.94 for C31:C32, and adjusted R 2 = 0.96 for C32:C33; P < 0.0001). FR of natural n -alkanes showed a coefficient of variation of about 15% and 16% for C31 and C33, respectively, in cattle. In sheep, the coefficient of variation was 8% and 14% for C31 and C33, respectively. The relationships between the difference of FR of n -alkane pairs and the error in feed intake estimation in cattle were characterized by an adjusted R 2 = 0.83 for C31:C32 ( P < 0.0001) and adjusted R 2 = 0.93 for C32:C33 ( P < 0.0001). In sheep, they were characterized by an adjusted R 2 = 0.69 for C31:C32 ( P < 0.001) and adjusted R 2 = 0.76 for C32:C33 ( P < 0.001). The n -alkane technique provided the reliability for estimating feed intake in cattle and sheep in barn experiments. The present meta-analysis demonstrated that without correction for differences in FR of n -alkane pairs, deviation in feed intake prediction would occur. However, further research is necessary to determine the relationship between the n -alkane dosing procedure (daily amount and duration of dosing) and FR of n -alkane.